UNDERSTANDING THE RUBRIC INSTRUMENT IN EVALUATING EFL LEARNING: A SYSTEMATIC ANALYSIS OF INTERNATIONAL PUBLICATIONS - Syarfuni; Maulizan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
This study aimed to interpret the rubric instrument's understanding in the assessment of English as a foreign language learning in Indonesia through a systematic review of the literature on international high-impact journal publications. The data were collected related literature from various online sources, including Google Scholar sources, ERIC publications, Google Docs, and other reading sources. Furthermore, we critically analyze starting from understanding the study questions and then reviewing the publication data involving the coding system, in-depth evaluation, and making valid conclusions and trustworthiness. Because this data relies on secondary data from published journals, we limit it to publications between 2010 and 2021. We do it in a descriptive qualitative design brought by the qualitative research expert's guidance from the data search process to reporting. Consider the existing literature; the findings include assessment rubrics that are usually used in teaching English as an instrument in the form of a matrix or grid, which describes the elements and criteria of a standard measuring instrument whose function is to assess student assignments clearly and transparently. The rubric in question is appropriate and in line with the learning outcomes programmed in specific terms.